SUSTAINABLE DEVELOPMENT PROJECTS – MANAGEMENT AND INVOLVEMENT IN THE EUROPEAN UNION - Radulescu Carmen, Valentina; Nastase, Marian (Economics of Agriculture, 2012)
Project management can be perceived as a science as and art or a technique, which cover a particular purpose. With Romanias return to market economy has been increasingly felt the need to achieve real projects, to achieve more structured and to justify requests for change, for improvement or financing something existing or proposed to establish. Sustainable development is a very complex concept, which started with concerns over the environment, the idea being enhanced over time with an economic and social dimension. Although initially meant to be a solution to ecological crisis caused by intense exploitation of resources and environmental degradation continues, today the concept is expanded of quality of life in its complexity, both in economic and social appearance. Structural Funds address sustainable development as horizontal aspects, is trying awareness on environmental protection.